Antioxidant properties of Carallia brachiata stem bark and leaf - Yenni Pintauli Pasaribu; Yorinda Buyang; Novike Bela Sumanik; La Hisa; Johanis Wairata (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Carallia brachiata (Lour.) Merr. (Rhizophoraceae) had been used to treat various human disoders. This study reported antioxidant activity of C. brachiata of stem bark and leaf in various solvents. Each sample was macerated in various solvent separately. By using DPPH, ABTS, and FRAP assays, antioxidant activity was determined. The TLC method was created using dichloromethane and ethyl acetate mobile phase. The methanol extract of stem bark contained the highest TPC value (262.73 ± 1.58 mg GAE/ g extract), while the methanol extract of leaf contained the highest TFC value (45.46 ± 0.32 mg QE/ g extract). The total phenolic content of stem bark extract was higher than that of leaf extract, but the flavonoid content of the leaf extract was marginally higher. The methanol extract exhibited the highest antioxidant activity for DPPH (13.06±0.08 μg/mL), ABTS (7.19±0.08 μg/mL), and FRAP assay (155.19±0.34 μM Fe2+/g). In this research, stem bark has greater antioxidant activity than the leaf. In addition, the results of TLC profile were detailed. The TLC chromatogram indicates that C. brachiata stem bark contains more components than leaf. This study indicates that C. brachiata has a rich source of prospective antioxidants.